Penggunaan Media Sosial dalam Perilaku Keagamaan Generasi Milenial di Kecamatan Rilau Ale Kabupaten Bulukumba - Muhammad Syahdarul Awal; Kamaluddin Tajibu; Fikri Alghifari Yunus (Liwaul Dakwah: Jurnal Kajian Dakwah dan Masyarakat Islam, 2026)
This study aims to describe how millennials in Bulukumba Regency's Rilau Ale Subdistrict use social media in relation to their religious practices.This study employs a descriptive qualitative approach with a sociological perspective. The primary data sources are several informants selected purposively, consisting of millennial generations aged 20-30 years in Rilau Ale Sub district. The data collection methods used were in depth interviews and field observations. Data reduction, data display, and conclusion-making were the methods used for data processing and analysis.Two main findings emergend. First, it has been demonstrated that using social media for religious outreach and education has a good effect, especially when it comes to improving religious knowledge, worship quality, and the millennial generation's involvement in religious activities. Second, careless and ineffective use can impair the practice of religious ideals and lessen the intensity of worship. The millennial generation’s differences in religious behavior suggest that people's use of social media greatly influences its efficacy. For the millennial generation to profit as much as possible, social media use must be appropriately guided. Therefore, it is critical to enhance religious understanding and digital literacy through the responsibilities of society, school, and the family.